2019
DOI: 10.1002/cbdv.201800609
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Tuber indicum from Different Geographical Regions of China

Abstract: Tuber indicum, an endemic truffle species in eastern Asian, is an edible mushroom that is both an important export and widely distributed across China. Many existing studies on truffles focus on analyzing their taxonomy, population genetics, volatile organic compounds and artificial cultivation of the truffles, while little information is available about their nutrient composition and pharmacological activity, especially the relationship between chemical composition in ascocarps and their geographic distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 73 publications
(69 reference statements)
1
18
0
Order By: Relevance
“…hirtum clones) were investigated by using 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), β-carotene bleaching, and oxygen radical absorbance capacity (ORAC) assays, and it was concluded that the geographical difference is a significant factor on the antioxidant activity of studied species. This phenomenon was also reported by several other researchers [ 153 , 154 , 155 ]. In addition to the geographical origin of the plant, harvesting time is another factor that may affect the antioxidant activity [ 156 ].…”
Section: Antioxidant Activities Of Essential Oilssupporting
confidence: 89%
“…hirtum clones) were investigated by using 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), β-carotene bleaching, and oxygen radical absorbance capacity (ORAC) assays, and it was concluded that the geographical difference is a significant factor on the antioxidant activity of studied species. This phenomenon was also reported by several other researchers [ 153 , 154 , 155 ]. In addition to the geographical origin of the plant, harvesting time is another factor that may affect the antioxidant activity [ 156 ].…”
Section: Antioxidant Activities Of Essential Oilssupporting
confidence: 89%
“…Moreover, the analyses are rapid and suitable for routine testing. The development and validation of the qualitative and quantitative LC-MS/MS method is frequently carried out, especially during plant or fungal chemotaxonomic studies, fingerprint analyses, or comparison of samples from different geographical regions [10][11][12]. There are many LC-MS methods created for the analyses of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms, depending on the stage of growth and morphological part (stipes or caps), are characterized by a different composition of sugars and organic acids, which mainly determine their flavor (Chen et al 2015). The content and profile of sugars and polyols may differ significantly in fruiting bodies of the same species but obtained from different sources (Li et al 2019;Stojković et al 2014).…”
Section: Introductionmentioning
confidence: 99%